(untitled) (City: History, Culture, Society, 2018)
The article describes the character of Mykola Hankevich in the context of the early parliamentary elections of 1908 in Galicia. The author sets out his task, by shifting the usual historiographical accents, to consider the general election culture in the provincial capital in the early twentieth century, the theory and practice of the international socialist movement in a multinational urban environment. The well-established point of view of K. Jobst and other researchers, who believe that the conflict over Hankevich’s face in the 1907 elections, when the executive leadership of the PPSD did not support his candidacy, is the beginning of the path that ultimately led the Polish and Ukrainian Social Democrats parties in the bosom of "their" national camps, and the ephemeral international socialist movement in Galicia disintegrated. The author believes that such a narrative simplifies the processes that took place in the environment of the Galician socialist parties. Cooperation between Ukrainian, Polish, and Jewish socialists did not stop until the outbreak of the First World War. In the USDP, M. Hankevich himself did not cease to cooperate closely with Polish and Jewish socialists. During the snap election of 1908, the PPSD leader agreed with the candidacy of Mykola Hankevich, who, however, lost this election by winning 734 votes against 1011. However, in the anti-Ukrainian hysteria that had not yet subsided after the assassination of Andrzej Potocki, more than 40% of the vote, loyal to the Ukrainian and socialist candidates in the bourgeois Lviv district, looked like a tremendous success for Hankevich. Having identified the main reasons for this success, namely: his impeccable personal reputation, eloquence, popularity among the Lviv workers and intellectuals, genuine internationalism and willingness to represent different ethnic groups and different social strata, the author, referring to the memories of the Polish socialist Yevhen Morachevsky, calls another circumstance that explains the results of the vote quite differently. It is about 450 votes that Morachevsky bought in favour of Gankevich. The author notes that Morachevsky considers his dubious act as a peculiar feat - to pollute his hands to achieve a noble political goal, in which, in his opinion, he manifests the instinct and ability of a politician, thereby opposing himself to "dreamers" and idealists who did not compromise own principles.